1999
DOI: 10.1037/0021-9010.84.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Structural equation models of sexual harassment: Longitudinal explorations and cross-sectional generalizations.

Abstract: Sexual harassment and its corresponding outcomes develop and change over time, yet research on this issue has been limited primarily to cross-sectional data. In this article, longitudinal models of harassment were proposed and empirically evaluated via structural equations modeling using data from 217 women who responded to a computerized questionnaire in 1994 and again in 1996. Results indicate that sexual harassment influences both proximal and distal work-related variables (e.g., job satisfaction, work with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
137
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(151 citation statements)
references
References 33 publications
8
137
1
Order By: Relevance
“…However, this study suffers from its exclusion of multiple forms of HDW and its limited measure of workplace aggression. Studies of single workplaces have found rates of GWH experiences ranging from 55% (Bjorkqvist, Osterman, & Hjelt-Back, 1994) to 75% (Rospenda, Richman, Wislar, & Flaherty, 2000).Another problem with existing research is that, with a few exceptions (Glomb, Munson, Hulin, Bergman, & Drasgow, 1999;Rospenda et al, 2000), HDW researchers have overlooked sources of stress from one's broader job context, and no studies to date have examined the effects of HDW in the context of non-work stressors, despite the fact that life stressors are associated with mental health (Pearlin, 1999) and alcohol use (Steffy & Laker, 1991). By neglecting alternate sources of stress, estimates of the overall effects of HDW on outcomes may be inaccurate.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…However, this study suffers from its exclusion of multiple forms of HDW and its limited measure of workplace aggression. Studies of single workplaces have found rates of GWH experiences ranging from 55% (Bjorkqvist, Osterman, & Hjelt-Back, 1994) to 75% (Rospenda, Richman, Wislar, & Flaherty, 2000).Another problem with existing research is that, with a few exceptions (Glomb, Munson, Hulin, Bergman, & Drasgow, 1999;Rospenda et al, 2000), HDW researchers have overlooked sources of stress from one's broader job context, and no studies to date have examined the effects of HDW in the context of non-work stressors, despite the fact that life stressors are associated with mental health (Pearlin, 1999) and alcohol use (Steffy & Laker, 1991). By neglecting alternate sources of stress, estimates of the overall effects of HDW on outcomes may be inaccurate.…”
mentioning
confidence: 84%
“…Another problem with existing research is that, with a few exceptions (Glomb, Munson, Hulin, Bergman, & Drasgow, 1999;Rospenda et al, 2000), HDW researchers have overlooked sources of stress from one's broader job context, and no studies to date have examined the effects of HDW in the context of non-work stressors, despite the fact that life stressors are associated with mental health (Pearlin, 1999) and alcohol use (Steffy & Laker, 1991). By neglecting alternate sources of stress, estimates of the overall effects of HDW on outcomes may be inaccurate.…”
Section: Shortcomings Of Existing Research On Hdwmentioning
confidence: 99%
“…Employees exposed to violence and threats at work also exhibit an increased risk of turnover intentions (Estryn-Behar et al 2008;LeBlanc and Kelloway 2002), and lower levels of organizational commitment and job satisfaction (Barling et al 2001). Similarly, exposure to sexual harassment is associated with low job satisfaction (Glomb et al 1999). Furthermore, all these acts of offensive behaviours have been found to affect health and psychological well-being (Glomb et al 1999;Hogh et al 2008Hogh et al , 2011aWieclaw et al 2006).…”
Section: Background and Objectivesmentioning
confidence: 96%
“…Similarly, exposure to sexual harassment is associated with low job satisfaction (Glomb et al 1999). Furthermore, all these acts of offensive behaviours have been found to affect health and psychological well-being (Glomb et al 1999;Hogh et al 2008Hogh et al , 2011aWieclaw et al 2006).…”
Section: Background and Objectivesmentioning
confidence: 98%
“…Sexual harassment by men toward women has dominated the sexual harassment research, the findings of which show that such harassment occurs more frequently in male-dominated organizations (Berdahl & Moore, 2006;Fitzgerald, Drasgow, Hulin, Gelfand, & Magley, 1997;Glomb, Munson, Hulin, Bergman, & Drasgow, 1999). Although researchers initially believed that the reason for this was that more men in the company of fewer women would naturally lead to higher levels of harassment, recent research has shown that sexual harassment occurs more frequently in these organizations because male-dominated organizations generally involve careers that are traditionally held by men (e.g., construction workers, military).…”
Section: Social Identity and Self-categorization Theories: Attackingmentioning
confidence: 99%